An innovative approach in teaching at Bicol Teachers College a case study - Hirsch, Francia (Villar) (s.n.], 1974)
The central problem of this thesis is to seek answers as to why a curricular innovation such as Education 14: Discovery Approach to Learning and Teaching has been discontinued in the Bicol Teachers College, BTC (now Bicol University College of Education). To do so, the following were determined: (1) the procedures involved in innovating a discovery course in a regional teacher training institution (2) the underlying motives of the students for taking the course (3) the expectations of the students, college and laboratory school instructors and administrators for the course (4) the comparison of the course with that of a non-discovery course using the lecture method (5) the differences in perception of the usefulness of the course in teacher-preparation by students, college and laboratory school instructors and administrators and (6) the improvements needed for an innovative course such as Education 14.